Analisis Praktik Pembelajaran Berdiferensiasi pada Mata Pelajaran PJOK di SD Negeri Kecamatan Gunungpati Kota Semarang - Amalinta Jibalul Ilma; Wahyu Ragil Kurniawan (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to analyze the practice of differentiated learning in Physical Education, Sports, and Health (PJOK) subjects in Public Elementary Schools in Gunungpati District, Semarang City. The study used a qualitative method with a descriptive approach. The research informants consisted of PJOK teachers and students at 18 Public Elementary Schools selected using a purposive sampling technique. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model which includes data reduction, data presentation, and conclusion drawing. The results showed that PJOK teachers' understanding of differentiated learning was still at various levels, namely good, sufficient, and limited categories. Teachers with a good understanding had implemented differentiation of content, process, and product through adjusting the level of material difficulty, using varied learning methods, and assessment based on student development. However, most implementations were still dominated by process differentiation, while product differentiation and the use of diagnostic assessments had not been carried out optimally. Identification of student learning needs was generally carried out through direct observation during learning and had not been supported by systematic assessment. The main obstacles identified included limited learning time, a relatively large student population, and teachers' unequal understanding of the concept of differentiated learning. The study's conclusions indicate that differentiated learning in Physical Education (PJOK) in public elementary schools in Gunungpati District has begun to be implemented and is aimed at meeting the diverse learning needs of students, but its implementation has not been systematic and consistent. Therefore, strengthening teacher competencies, utilizing diagnostic assessments, and providing school support are needed to improve the quality of differentiated learning implementation in PJOK.